Use of the autopericardial valve conduit in a infants in surgical correction of the common arterial trunk (case report) - Lekan, R.; Buzovskiy, V.; Bosenko, V.; Pengrina, I.; Lekan, I.; Popsuiko, A.; Rudometkin, O.; Buriachenko, I.; Zhekov, N. (Ukrainian Journal of Cardiovascular Surgery, 2016)
There was operated a newborn had common arterial trunk at the cardiosurgery department of Odessa Regional Children Hospital in august 2015. It was made outflow tract reconstruction of the right ventricle by personally prepared autopericardial valve conduit, diameter and a length of this one 12mm x 55 mm. In the long term, 6 months later, it notes satisfactory condition with good hemodynamic parameters of functioning of the valve conduit, maximum systolic gradient is 20 mm Hg. There is no regurgitation on the valve and no reshunt on VSD. It is insignificant regurgitation on the aortic valve.